Editorial: Special Issue “Thermo-Mechanical and Electrical Measurements for Energy Systems: 1st Edition” - Emanuele Rizzuto; Ludovica Apa; Livio D’Alvia (Energies, 2025)
Over the last decade, rapid technological advances have accelerated the development and application of various measurement solutions in energy systems [...]